IMPLEMENTASI SISTEM PENERANGAN DAN PROTEKSI PANEL SURYA KERAMBA JARING APUNG PADA KELOMPOK NELAYAN KAMPUNG BUGIS DI KOTA KOTAMADYA TANJUNG PINANG - Kusuma, Hollanda Arief; Refly, Septia; Pramana, Rozeff (Jurnal Hilirisasi IPTEKS, 2024)
The fishing community in Kampung Bugis, Tanjungpinang, faces difficulties in accessing electricity at night, which negatively impacts their fishing productivity and increases the risk of accidents at the floating fish cages. Currently, they still rely on generators, while the potential utilization of solar panels as a renewable energy source has not been optimally realized. The main challenge in applying solar panels in this location is the risk of damage due to the harsh maritime environment, as well as concerns about theft due to the lack of adequate protection. This activity aims to improve fishermen's access to electricity by implementing a solar-based lighting system equipped with additional protection to ensure its security. The project involved several phases, starting from problem identification, preparation of tools and materials, installation of solar panels with specially designed iron protection frames, to assistance to ensure that fishermen understand how to use and maintain the system. The installation process was conducted with the fishermen’s involvement, allowing them to maintain the system independently. The results showed that the solar-powered lighting system provided stable lighting at night, reduced the fishermen’s dependence on generators, and increased their productivity in fishing activities. Additionally, the protection provided for the solar panels successfully reduced the risk of damage and theft, which had previously been a major concern. In conclusion, this technological solution effectively improved energy access and the fishermen’s productivity, while providing long-term impact on the sustainability of the floating fish cage operations. For the program's sustainability, regular monitoring and system capacity enhancement are recommended in the future.